Agri-product evaluation and biodiversity measurement - Kovács, Szilvia (Applied Studies in Agribusiness and Commerce, 2011)
This paper is meant to be the first part of a two part unit that will be published next. The objective of this paper is to be an introduction of agri-product evaluation, within which a short summary of essentials of diversity measurement is given and to share experience on evaluation of environmental friendly agri-product. For biodiversity measurement and extern effects, literature of related publications was processed and experience gained over experimental projects on environmental-friendly technologies was summed up. Methods applied were based on influence-response approach which guided us all through the research work. It can be stated that one diversity measure or one diversity function fails to describe communities of living beings; therefore, at least two methods should be used in parallel. Scale-dependent description of diversity is necessary, which provides us with new information that can not be revealed by traditional methods. To identify external effects, we have to take influences of use of a specific product into account and the responses generated by use of that product. Influences might appear in parallel or can build up one another, similarly to the generated responses of environment. To be as precise as possible, it is suggested that we take into account only clear responses. Influence response relations are shown here using terms and concepts in broad sense and in general. More sophisticated application of terms and concepts is needed to evaluate properly and in monetary terms.We will make efforts to clarify terms and their use in the future.